Analysis of the human HSP70-HSP90 organising protein (HOP) gene - characterisation of the promoter and identification of a novel isoform - Mattison, Stacey (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2018)
Expected release date-April 2020
Keywords: Uncatalogued